EVALUASI KEBIJAKAN PENANGANAN KONFLIK SOSIAL DI KECAMATAN MOUTONG KABUPATEN PARIGI MOUTONG - Rukli, Rukli (Katalogis, 2018)
This study aims to find out the implementation of Social Conflict Handling in Moutong Sub-district of Parigi Moutong Regency through Qualitative Descriptive Approach based on model of Logical Framework Approach (LFA) Evaluation Approach According to WK Kellog Foundation, with 5 (five) analysis tools such as Input , Activities, Output, Outcome, and Impact, the number of informants as many as 8 (eight) people, determined by informants who know the problems studied. Data collection is done by observation, interview, and documentation. Based on the results of research and discussion, that the implementation of Social Conflict handling program implemented by the Ministry of Social Affairs with social harmony program in Moutong Sub-district has been running in accordance with the program plan. This is evidenced by the absence of conflicts that occurred within the last 4 (four) years, has established a harmonious relationship between the people of the village of Lobu and the village of East Moutong.